1988
DOI: 10.1021/bi00422a023
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of monoamine oxidase A by the monoamine oxidase B inactivators 1-phenylcyclopropylamine, 1-benzylcyclopropylamine, and N-cyclopropyl-.alpha.-methylbenzylamine

Abstract: Three known mechanism-based inactivators of beef liver mitochondrial monoamine oxidase (MAO) B are tested as inactivators of human placental mitochondrial MAO A. 1-Phenylcyclopropylamine (1-PCPA), 1-benzylcyclopropylamine (1-BCPA), and N-cyclopropyl-alpha-methylbenzylamine (N-C alpha MBA) are time-dependent irreversible inactivators of MAO A. The KI values for 1-PCPA and N-C alpha MBA, analogues of the MAO B substrate benzylamine, are much higher with MAO A than with MAO B. Evidence is presented to show that 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Since the calculated stability trend of adduct models in the aqueous phase confirms experimental findings, rather than in the gas phase, it is reasonable to assume that the proposed adducts can form with residues that are close to the surface of MAOs, which are expected to be in more hydrophilic environment. According to Silverman & Hiebert 23 , cys365 in MAO-B and the corresponding amino acid cys374 in MAO-A are logical candidates which are on the surface of the protein. The results of our calculations in aqueous solution are consistent with this rationale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the calculated stability trend of adduct models in the aqueous phase confirms experimental findings, rather than in the gas phase, it is reasonable to assume that the proposed adducts can form with residues that are close to the surface of MAOs, which are expected to be in more hydrophilic environment. According to Silverman & Hiebert 23 , cys365 in MAO-B and the corresponding amino acid cys374 in MAO-A are logical candidates which are on the surface of the protein. The results of our calculations in aqueous solution are consistent with this rationale.…”
Section: Resultsmentioning
confidence: 99%
“…Although the structure of the inactivated enzyme adduct (4) has not known, the X group in (4) could be either the flavin semiquinone formed in the first step or an amino acid radical generated from hydrogen atom transfer from the amino acid to the flavin semiquinone. Two experiments identified this amino acid to be a cysteine residue 22 , cys365 in MAO-B being a logical candidate 23,24 . However, elucidation of the structure of human MAO-B 25 and MAO-A 26,27 and of rat MAO-A 28 by X-ray revealed that there is no cysteine in the active site; cys365 in MAO-B and the corresponding amino acid cys374 in MAO-A are on the surface of the protein.…”
Section: Introductionmentioning
confidence: 99%
“…Right: the C4a adduct as deduced from the MAO Atranylcypromine crystal structure [122]. several interpretations [276][277][278][279], but the crystal structure of TCP-MAO B at 1.9 Å resolution is clearly C4a [122]. Studies on flavin modification continues in other flavoenzymes, providing insight into the formation of N5 and C4a adducts.…”
Section: Visible Spectra and Ligand Binding To Maomentioning
confidence: 99%
“…The adduct formed changes with the derivative used and can be different for MAO A. With MAO B, 1-phenylcyclopropylamine (1-PCPA) forms a mixture of the N5 and cysteine adducts [284]; with MAO N, it forms some C4a but mainly the N5 adduct [280]; and with MAO A it forms the N5 adduct [179,279]. As discussed above, inactivation of MAO B with 2-PCPA gives the C4a adduct in the crystal structure despite evidence for a mixture of adducts from the spectral and radioligand binding experiments.…”
Section: Visible Spectra and Ligand Binding To Maomentioning
confidence: 99%
“…In contrast, nonfluorinated 38 is known to be a weak and moderately selective (A:B = 0.26:1) inhibitor of MAO B. [64] Thus, introduction of a fluorine substituent in position 2, trans to the amino group, caused a dramatic reversal of isoform selectivity to give A versus B selectivity of 135:1.…”
Section: Inhibition Of Flavin-dependent Amine Oxidases Mao a And B Bymentioning
confidence: 99%